Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Nguyễn Châu Anh
Xem chi tiết
Trần Thanh Hải
Xem chi tiết
Nguyễn Lê Phước Thịnh
16 tháng 3 2023 lúc 18:36

loading...  

Thuỳ Linh Nguyễn
16 tháng 3 2023 lúc 18:43

\(a,-3x^2+7x-9+\left(x-1\right)\left(x+2\right)\\ =-3x^2+7x-9+x^2-x+2x-2\\ =\left(-3x^2+x^2\right)+\left(7x-x+2x\right)-\left(9+2\right)\\ =-2x^2+8x-11\\ b,x\left(x-5\right)-2x\left(x+1\right)\\ =x^2-5x-2x^2-2x\\ =\left(x^2-2x^2\right)-\left(5x+2x\right)\\ =-3x^2-7x\\ c,4x\left(x^2-x+1\right)-\left(x-1\right)\left(x^2-x\right)\\ =4x^3-4x^2+4x-x\left(x^2-x\right)+x^2-x\\ =4x^3-4x^2+4x-x^3+x^2+x^2-x\\ =\left(4x^3-x^3\right)+\left(-4x^2+x^2+x^2\right)+\left(4x-x\right)\\ =3x^3-2x^2+3x\\ =x\left(3x^2-2x+3\right)\)

\(d,-5x\left(x-5\right)+\left(x-3\right)\left(x^2-7\right)\\ =-5x^2+25x+x\left(x^2-7\right)-3\left(x^2-7\right)\\ =-5x^2+25x+x^3-7x-3x^2+21\\ =\left(-5x^2-3x^2\right)+\left(25x-7x\right)+x^3+21\\ =-8x^2+x^3+18x+21\)

Nguyễn Linh
Xem chi tiết
Thanh Hằng
31 tháng 12 2020 lúc 14:06

(\(3+\dfrac{x}{3-x}+\dfrac{2x}{3+x}-\dfrac{4x^2-3x-9}{x^2-9}\) ):\(\left(\dfrac{2}{3-x}-\dfrac{x-1}{3x-x^2}\right)\)\(=\left(\dfrac{3x^2-27}{\left(x-3\right)\left(x+3\right)}+\dfrac{-x\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}+\dfrac{2x\left(x-3\right)}{\left(x-3\right)\left(x+3\right)}-\dfrac{4x^2-3x-9}{\left(x-3\right)\left(x+3\right)}\right)\)\(:\left(\dfrac{2x}{x\left(3-x\right)}-\dfrac{x-1}{x\left(3-x\right)}\right)\)

\(=\dfrac{3x^2-27-x^2-3x+2x^2-6x-4x^2+3x+9}{\left(x-3\right)\left(x+3\right)}:\dfrac{x+1}{x\left(3-x\right)}\) 

\(=\dfrac{-6x-18}{\left(x-3\right)\left(x+3\right)}:\dfrac{x+1}{x\left(3-x\right)}\) \(=\dfrac{-6\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}:\dfrac{x+1}{x\left(3-x\right)}\) 

\(=\dfrac{6}{3-x}.\dfrac{x\left(x-3\right)}{x+1}\) \(=\dfrac{6x}{x+1}\)

Thanh Nga Nguyễn
Xem chi tiết
Nguyễn Thị Thảo
26 tháng 7 2017 lúc 10:50

(=) (x+3)^2. (x-3)^2.(x-3).(x+3)

(=) (x+3)^3 . (x-3)^3 

dấu . là dấu  nhân nhé bn 

Dung Trần
Xem chi tiết
Ngô Quốc Thịnh
Xem chi tiết
YangSu
25 tháng 6 2023 lúc 14:00

\(A=\left(\dfrac{3x-x^2}{9-x^2}-1\right):\left(\dfrac{9-x^2}{x^2+x-6}+\dfrac{x-3}{2-x}-\dfrac{x+2}{x+3}\right)\left(dk:x\ne\pm3,x\ne2\right)\)

\(=\dfrac{3x-x^2-9+x^2}{9-x^2}:\left(\dfrac{9-x^2}{\left(x-2\right)\left(x+3\right)}-\dfrac{x-3}{x-2}-\dfrac{x+2}{x+3}\right)\)

\(=\dfrac{3x-9}{9-x^2}:\dfrac{9-x^2-\left(x-3\right)\left(x+3\right)-\left(x+2\right)\left(x-2\right)}{\left(x-2\right)\left(x+3\right)}\)

\(=-\dfrac{3\left(x-3\right)}{\left(x-3\right)\left(x+3\right)}.\dfrac{\left(x-2\right)\left(x+3\right)}{9-x^2-\left(x^2-9\right)-\left(x^2-4\right)}\)

\(=-\dfrac{3}{x+3}.\dfrac{\left(x-2\right)\left(x+3\right)}{9-x^2-x^2+9-x^2+4}\)

\(=\dfrac{-3\left(x-2\right)}{22-3x^2}\)

\(=\dfrac{-3x+6}{22-3x^2}\)

Vậy \(A=\dfrac{-3x+6}{22-3x^2}\) với \(x\ne\pm3,x\ne2\)

êrgsrgrg
Xem chi tiết
Nguyễn Hoàng Minh
24 tháng 9 2021 lúc 14:41

\(i,=\left(x-3\right)\left(x+3\right)^2-\left(x-3\right)\left(x^2+3x+9\right)\\ =\left(x-3\right)\left(x^2+6x+9-x^2-3x-9\right)\\ =3x\left(x-3\right)=3x^2-9x\\ ii,=x^3-8-25-x^3=-33\)

Nguyễn Lê Phước Thịnh
24 tháng 9 2021 lúc 14:45

ii: Ta có: \(\left(x-2\right)\left(x^2+2x+4\right)-\left(x^3+25\right)\)

\(=x^3-8-x^3-25\)

=-33

Nguyễn Thị Khánh Huyền
Xem chi tiết
Trần Ngọc Bảo Hân
Xem chi tiết
Hải Đức
25 tháng 7 2021 lúc 17:23

a, `(x-3)(x^2+3x+9)-(x^2-1)(9x+27)`

`=x^3-3^3-(9x^3+27x^2-9x-27)`

`=x^3-3^3-9x^3-27x^2+9x+27`

`=-8x^3-27x^2+9x`

b, `(x-2)(x^2+2x+4)-x(x-3)(x+3)`

`=x^3-2^3-x(x^2-9)`

`=x^3-8-x^3+9x`

`=9x-8`

Nguyễn Lê Phước Thịnh
25 tháng 7 2021 lúc 19:33

a) Ta có: \(\left(x-3\right)\left(x^2+3x+9\right)-\left(x^2-1\right)\left(9x+27\right)\)

\(=x^3-27-\left(9x^3+27x^2-9x-27\right)\)

\(=x^3-27-9x^3-27x^2+9x+27\)

\(=-8x^3-27x^2+9x\)

b) Ta có: \(\left(x-2\right)\left(x^2+2x+4\right)-x\left(x-3\right)\left(x+3\right)\)

\(=x^3-8-x\left(x^2-9\right)\)

\(=x^3-8-x^3+9x\)

\(=9x-8\)